2020
DOI: 10.18280/ti-ijes.642-402
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology of Energy Optimization in Indoor Swimming Pool

Abstract: Swimming pools require a large amount of energy to provide comfort for the swimmers, therefore, energy saving actions must be studied in order to optimise their efficiency even when the existing systems are already of high performance. The case study relies on a public indoor swimming pool, in which dynamic simulations were developed by using TRNSYS software. Experimental measurement campaign was also performed in order to investigate the system operation to calibrate the numerical model by using the real data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In order to make a comparison of the possible layouts of the HP system, a simulation has been carried out considering only the AWHP. This layout is similarly to what has been analyzed in the previous work on the same swimming Pool Centre [30]. The difference in terms of contribution to the thermal power plant and energy performance of the systems are summarized in Table 7.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…In order to make a comparison of the possible layouts of the HP system, a simulation has been carried out considering only the AWHP. This layout is similarly to what has been analyzed in the previous work on the same swimming Pool Centre [30]. The difference in terms of contribution to the thermal power plant and energy performance of the systems are summarized in Table 7.…”
Section: Resultsmentioning
confidence: 87%
“…Similarly to the study reported in [30], several dynamic simulations have been carried out using TRNSYS simulation tool. The energy model of the existing building and plant was calibrated in the previous study by means of monitoring data recorded during the winter period.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations